Clinicopathological features of colorectal polyps and risk of colorectal cancer in acromegaly. Issue 3 (March 2020) - Ochiai, Yorinari; Inoshita, Naoko; Iizuka, Toshiro; Nishioka, Hiroshi; Yamada, Shozo; Kitagawa, Masanobu; Hoteya, Shu
Abstract : Objective: Patients with acromegaly are at increased risk of colorectal polyps. However, their risk of colorectal cancer remains unclear. This study aimed to identify the histopathological features of colorectal polyps in patients with acromegaly and compare their risk of colorectal cancer with that in healthy controls. Methods: The study participants were 178 patients who underwent Hardy's operation and perioperative colonoscopy at our hospital between April 2008 and September 2016. For the control group, we randomly selected 356 age- and sex-matched patients who underwent colonoscopy at our hospital during the same period. The incidence, size, location, and histology of the colorectal polyps detected were compared between the groups. Results: Colorectal polyps were detected in 66.8% of the acromegaly group and 24.2% of the control group ( P  < 0.001). The average number and size of the polyps were 2.44 and 4.74 mm, respectively, in the acromegaly group and 1.77 and 3.89 mm in the control group ( P  = 0.001). Polyps in the acromegaly group were more likely to be in the rectosigmoid region ( P  = 0.006). In the acromegaly group, the frequency of polyps ≥5 mm was 34.3% and that for polyps ≥10 mm was 15.2%; the respective values were 7.6% and 2.2% in the control group ( P  < 0.001). We found no evidence of between-group histopathological differences in the polyp specimens resected by endoscopy. Conclusions: Patients with acromegaly are at an increased risk of colorectal polyps, especially in the rectosigmoid region. However, there is no pathological evidence that they are at greater risk of colorectal cancer than the general population.